Comparison of AlN Encapsulants for Bulk GaN Multicycle Rapid Thermal Annealing. (1st January 2015) - Greenlee, Jordan D.; Anderson, Travis J.; Feigelson, Boris N.; Wheeler, Virginia D.; Hobart, Karl D.; Kub, Francis J.
Abstract : Sputtered AlN capping layers deposited at different temperatures were compared for their efficacy in protecting bulk GaN substrates during high temperature annealing. AlN sputtered at a substrate temperature of 400°C on the epi-ready surface of bulk GaN cracked due to the strain associated with the lattice mismatch between AlN and GaN. AlN caps sputtered on the rougher optically-polished surface did not crack due to strain relief that results from polishing damage. During heating pulses with a maximum temperature of 1400°C, the exposed GaN in the cracked regions was damaged due to GaN decomposition. In contrast, AlN capping layers deposited at room temperature did not exhibit cracking since this condition energetically prevents the AlN from orienting to the GaN surface and forming cracks. Even after 20 rapid heating cycles with a maximum temperature of 1400°C, the GaN surface remains very smooth (0.70 nm RMS) over a 350 μm × 260 μm area. The ability to anneal bulk GaN at high temperatures without surface degradation using the AlN cap developed herein is a critical processing step that will enable planar processing for future vertical III-nitride devices.